GhWRKY70D13 Regulates Resistance to Verticillium dahliae in Cotton Through the Ethylene and Jasmonic Acid Signaling Pathways - Xiong, Xian-Peng; Sun, Shi-Chao; Zhang, Xin-Yu; Li, Yan-Jun; Liu, Feng; Zhu, Qian-Hao; Xue, Fei; Sun, Jie (Frontiers in Plant Science, 2020)
Verticillium wilt is a destructive cotton disease causing severe yield and quality losses worldwide. WRKY transcription factors play important roles in plant defense against pathogen infection. However, little has been reported on the functions of WRKYs in cotton’s resistance to Verticillium dahliae that causes Verticillium wilt. Here, we identified WRKY70 genes in Gossypium hirsutum, G. arboreum and G. raimondii, and investigated the expression profiles of all GhWRKY70 genes in various cotton tissues and in response to hormone treatment or V. dahliae infection. Knock-down of GhWRKY70D13 improved resistance to V. dahliae in both resistant and susceptible cotton cultivars. Based on comparative analysis of transcriptomes generated from wild-type and stable RNAi (RNA interference) plant with down-regulated GhWRKY70D13, genes involved in ethylene (ET) and jasmonic acid (JA) biosynthesis and signaling were significantly upregulated in the GhWRKY70D13 RNAi plants. Consistently, the contents of 1-aminocyclopropane-1-carboxylic (ACC), JA and JA-isoleucine levels were significantly higher in the GhWRKY70D13 RNAi plants than in wild-type. Following V. dahliae infection, the levels of ACC and JA decreased in the GhWRKY70D13 RNAi plants but still significantly higher (for ACC) than that in wild-type or at the same level (for JA) as wild-type. Collectively, our results suggested that GhWRKY70D13 negatively regulates cotton’s resistance to V. dahliae mainly through the ET and JA biosynthesis and signaling pathways